Development and implementation of clinical mentorship in Rwanda: successes and challenges - Jackson Sebeza; David J. Riedel; Athanase Kiromera; Marie-Claude C. Lavoie; Natalia Blanco; Taylor Lascko; Ribakare Muhayimpundu; Emma Mtiro; Placidie Mugwaneza; Habimana Dominique Savio; Cyprien Baribwira (Journal of Public Health in Africa, 2022)
Rwanda has prioritized the decentralization and integration of HIV services over the past decade to ensure universal access to HIV services throughout the nation. Improving the capacity of healthcare providers to provide high-quality HIV prevention and treatment services was a crucial component of this process. In partnership with the authors, Rwanda’s national health implementation agency developed a national clinical mentorship program from 2011 to 2017 to facilitate this transition. The Rwanda Clinical Mentorship Model aims to effectively manage HIV-infected patients across all levels of healthcare delivery, implement task shifting, and adhere to national guidelines. The clinical care of HIV-positive individuals was transferred from HIV specialists to family physicians and nurses. The facility team was trained, supervised, and mentored by a multidisciplinary team. Mentorship consisted of routine site visits during which clinical case reviews, clinical supervision teaching, and data reviews were conducted to assess the facility’s performance and identify obstacles. Between 2012 and 2020, 5,774 healthcare professionals across the country received HIV testing and treatment training. This clinical mentoring has demonstrated a pragmatic, data-driven, and enduring strategy for enhancing clinical practice at all levels of care. A dedicated cadre of mentors is required to ensure the coordination and sustainability of this approach, according to one finding. The authors participated in accelerating the geographic and scope expansion of clinical mentoring in Rwanda. Developing a sustainable HIV clinical mentorship program in Rwanda requires longterm partnerships and evolving technical assistance.